2017
DOI: 10.3389/fimmu.2017.00013
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Newborn Mice Accelerates the Architectural Maturation of Lymph Nodes, But AID-Dependent IgG Responses Are Still Delayed Compared to the Adult

Abstract: Lymph nodes (LNs) have evolved to maximize antigen (Ag) collection and presentation as well as lymphocyte proliferation and differentiation—processes that are spatially regulated by stromal cell subsets, including fibroblastic reticular cells (FRCs) and follicular dendritic cells (FDCs). Here, we showed that naïve neonatal mice have poorly organized LNs with few B and T cells and undetectable FDCs, whereas adult LNs have numerous B cells and large FDC networks. Interestingly, immunization on the day of birth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
0
18
1
Order By: Relevance
“…Although CAF01 can elicit fully established GCs in neonates (30) its effect on neonatal FDC-M2 + FDC maturation has not been reported. Others have proposed the role of FDC-M1 + FDCs (56, 57) and CR1 (56, 58) in the organization of B cell follicles and maintenance of GC in early life, whereas our previous work did not indicate that they were limiting factors for FDC network maturation (9). In agreement with our results, i.p.…”
Section: Discussioncontrasting
confidence: 80%
“…Although CAF01 can elicit fully established GCs in neonates (30) its effect on neonatal FDC-M2 + FDC maturation has not been reported. Others have proposed the role of FDC-M1 + FDCs (56, 57) and CR1 (56, 58) in the organization of B cell follicles and maintenance of GC in early life, whereas our previous work did not indicate that they were limiting factors for FDC network maturation (9). In agreement with our results, i.p.…”
Section: Discussioncontrasting
confidence: 80%
“…It was speculated that acetate could be released into the host hemolymph and delivered into fat body cells as substrates for fatty acid synthesis. It has been extensively studied that some short-chain fatty acids, including acetate, produced by intestinal symbiotic bacteria can regulate the fatty acids synthesis of the mammalian host [ 37 ], but more details need to be determined about how facultative endosymbionts synthesize short-chain fatty acids in aphids. Furthermore, we also found that lipogenesis genes were highly expressed in the fat body, suggesting that peripheral sheath cells of the bacteriomes where Serratia is located may interact with the scattered fat body cells in the aphid hemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…GC development requires structural organization by a network of follicular dendritic cells (FDCs) and follicular reticular cells (FRC), which are not fully mature during the early postnatal period [ 61 , 62 ]. The hampered ability to organize the anatomic architecture required for a GC reaction appears to not only delay the onset, but also limit persistence and diminish the magnitude of affinity matured antibody responses in newborn mice [ 63 ]. FDC immaturity is also associated with diminished availability of captured and displayed immune complexes in the GC, further limiting the capacity of B cells to take up and present antigen to acquire T cell help.…”
Section: The Antibody Response Of Young Infantsmentioning
confidence: 99%